Comparative Analysis of Linear Regression Method with Weighted Moving Average in Goods Sales Forecasting - Astuti, Novi; Yupianti , Yupianti; Prahasti, Prahasti (Jurnal Komputer, 2022)
Chandra Talo Building Store is one of the building shops located in Seluma Regency, Bengkulu Province. The store sells various kinds of building materials, from cement, paint, nails, wood, and others. So far, the management of data on materials, starting from recording inventory and selling goods, is still done manually through bookkeeping and notes, because there is no specific application that can help manage this data. The Goods Sales Forecasting Application at the Chandra Talo Building Store is built on an Android basis which can be accessed via an Android smartphone. The Goods Sales Forecasting application at the Chandra Talo Building Store was made in order to assist the Store in determining the amount of building materials to be restocked, by analyzing the time series on building material sales data that occurs every month which will produce a forecast or estimate of the amount of building materials to be restocked. Based on a comparative analysis of the Linear Regression Method and the WeightMovingAverage Method through the MAPE Method and the MSE Method, the results of the Linear Regression Method have a smaller error value than the WeightMovingAverage Method. Based on the system testing that has been done, it can be concluded that the functionality of the goods sales forecasting application at the Android-based Chandra Talo Building Store has been running well and can provide output reports on the results of forecasting sales of goods.